The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.4161/cc.4.6.1693
|View full text |Cite
|
Sign up to set email alerts
|

The Aurora A and Aurora B Protein Kinases: A Single Amino Acid Difference Controls Intrinsic Activity and Activation by TPX2

Abstract: The Aurora A and B protein kinases are key players in mitotic control and the etiology of human cancer. Despite the near identity of amino acid sequence in the catalytic domain, monomeric Aurora B is 50 fold lower in activity than monomeric Aurora A, and previous studies have shown that TPX2 binding to the catalytic domain activates Aurora A but not Aurora B. Here we identify G205 in Xenopus Aurora A as a key determinant of both intrinsic activity and regulation by TPX2. Mutation of G205 in Aurora A to N, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 38 publications
4
41
0
Order By: Relevance
“…S2 A). Consistent with previous reports (29,30), the kinase activity of Aurora-A G198N was reduced by 10-fold compared with that of Aurora-A WT (Fig. S3).…”
supporting
confidence: 81%
See 1 more Smart Citation
“…S2 A). Consistent with previous reports (29,30), the kinase activity of Aurora-A G198N was reduced by 10-fold compared with that of Aurora-A WT (Fig. S3).…”
supporting
confidence: 81%
“…Because the protein sequences of their catalytic domains are very similar, we are interested in understanding how distinct localization and function are determined. Although it has been reported that G198 in human Aurora-A (29) [G205 in Xenopus (30)] is a determinant for its regulation by TPX2 in vitro, the molecular mechanism and the biological effects of the G-N mutation were unknown. Here, we propose that the G-N mutation converts Aurora-A into Aurora-B-like kinase in cell (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, AurA (G198N) was capable of compensating for the loss of AurB function by forming a complex with INCENP and Survivin and localizing to the inner centromere and the spindle midzone in a manner dependent on its interaction with the components of the CPC. [49][50][51][52] Taken together, these data suggest that the different spatio-temporal distribution and biological functions of AurA and AurB are primarily determined by the nature of their interacting cofactors. If so, can such cofactors, while targeting AurA and AurB to different cellular compartments, still use similar strategies to regulate the kinase activity?…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 79%
“…2D), also blocked the phosphorylation of Aurora B on Thr232, which is required for Aurora B phosphotransferase activity. 24,25 We next turned our attention to two putative Aurora A substrates in VX-680-treated cells. The phosphorylation of Aurora A substrates is undetectable in an asynchronous cell population, but Aurora A becomes phosphorylated and activated on Thr288 in mitosis, [26][27][28] when Aurora A phosphorylates the centrosomal protein TACC3/ maskin on Ser558 (human numbering) in both human and Xenopus systems.…”
Section: Resultsmentioning
confidence: 99%